Microplasticity of idealized single crystalline Ag cantilevers characterized with methods of high resolution - Wobrock, Mark (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
Single crystalline, µm-sized cantilevers are fabricated out of epitaxially grown Ag thin films by a lithography-based procedure and are deflected by a nanoindenter system. The microstructure of the plastically deformed cantile-vers is investigated using transmission Kikuchi diffraction (TKD) on the cantilever cross section. 3D discrete dislocation dynamics simulations (DDD) are performed for further analysis. A mechanism to explain the formation of dislocation networks upon loading is suggested.